NONSPESİFİK BOYUN AĞRILI HASTALARDA D VİTAMİNİ DÜZEYİ - DİNÇ, SEMRA (Fırat Üniveristesi, 2021)
Bu çalışmanın amacı nonspesifik boyun ağrılı (NBA) hastalarda D vitamini düzeyinin belirlenmesidir. Araştırmaya Fırat Üniversitesi Tıp Fakültesi Hastanesi Fiziksel Tıp ve Rehabilitasyon polikliniğine boyun ağrısı şikayetiyle başvuruda bulunan ve NBA tanısı konulmuş ve D vitamini düzeyi incelenmiş 120 hasta dahil edilmiştir. Hastalardan yaş, boy, kilo, medeni hal, eğitim durumları, hastalık süresi, sigara ve alkol kullanımının olup olmadığı, nonsteroid antiinflamatuar ajan kullanımı bilgileri istenmiştir. Hastaların boy ve kilo ölçümünden vücut kitle indeksi (VKI) hesaplanmıştır. Hastaların Visual Analog Skala (VAS) ve Boyun Disabilite İndeksi (BDI) değerlendirilmiştir. Aynı zamanda hastalara Bournemouth Boyun Ağrısı Anketi ve Nottingham Sağlık Profili (NSP) anketi uygulanmıştır. Hastaların yaş ortalaması 33,8±8,3 (18,0-50,0) olarak bulunmuştur. Hastaların 43'ü (%35,8) erkek, 77'si (%64,2) ise kadındır. Hastaların 76'sında (%63,3) D vitamini eksikliği tespit edilmiştir, 44'ünde (%36,7) D vitamini düzeyi normal sınırlarda bulunmuştur. Erkeklerin 19 (%44,2)'unda, kadınların ise 57 (%74,0)'sinde D vitamini eksikliği görülmüştür. Kadınlardaki D vitamini eksikliği oranı erkeklerdekinden anlamlı şekilde fazla bulunmuştur (p=0,001). Gruplar arasında VAS skoru, BDI sorgulaması, Bournemouth anket sonuçları ve NSP puanları karşılaştırılmasında anlamlı farklılık görülmemiştir (p>0,05). Gruplar arasında BDI kategorisi açısından anlamlı farklılık görülmemiştir (p=497). Sonuç olarak non spesifik boyun ağrısı olan hastalarda D vitamini düzeyini ve etkilerini araştırdığımız, literatürde bir ilk olan çalışmamızda hastaların %63,3'ünde D vitamini eksikliği tespit edilmiş olup bu oran kadın hastalarda daha yüksektir. D vitamini eksikliğinin nonspesifik boyun ağrılı hastaların genelinde ağrı düzeyi, disabilite ve genel sağlık profili üzerine anlamlı etkisi bulunmadığı ortaya çıkarılmıştır. Anahtar kelimeler: Non spesifik boyun ağrısı, D vitamini, VAS, BDI, NSP

VITAMIN D LEVEL IN PATIENTS WITH NONSPECIFIC NECK PAIN The aim of this study is to determine the vitamin D level in patients with nonspecific neck pain. The study included 120 patients who applied to the Physical Medicine and Rehabilitation outpatient clinic of Fırat University Hospital with neck pain complaints and were diagnosed with NBA and whose vitamin D levels were examined. Information on age, height, weight, marital status, education status, duration of illness, smoking and alcohol use, and use of nonsteroidal anti-inflammatory agents were requested from the patients. Body mass index (BMI) was calculated from the height and weight measurements of the patients. Visual Analogue Scale (VAS) and Neck Disability Index (NDI) of the patients were evaluated. At the same time, Bournemouth Neck Pain Questionnaire and Nottingham Health Profile (NHP) questionnaire were applied to the patients. The mean age of the patients was found to be 33,8±8,3 (18,0-50,0). 43 (35,8%) of the patients are male and 77 (64,2%) of them are female. Vitamin D deficiency was found in 76 (63,3%) of the patients, and the vitamin D level was found within normal limits in 44 (36,7%) of them. Vitamin D deficiency was observed in 19 (44,2%) of men and 57 (74,0%) of women. The rate of vitamin D deficiency in women was significantly higher than in men (p = 0,001). There was no significant difference between the groups in the comparison of VAS score, NDI inquiry, Bournemouth questionnaire results and NHP scores (p> 0,05). There was no significant difference between the groups in terms of NDI category (p=497). As a result, in our study, which is the first in the literature in which we investigated the vitamin D level and effects of vitamin D deficiency in patients with non-specific neck pain, vitamin D deficiency was detected in 63,3% of the patients, and this rate was higher in female patients. It has been revealed that vitamin D deficiency has no significant effect on pain level, disability and general health profile in patients with nonspecific neck pain. Keywords: Nonspecific neck pain, vitamin D, VAS, NDI, NHP
Vitamin D level in patients with nonspecific neck pain
Keywords: Fiziksel Tıp ve Rehabilitasyon